RESPONS PERTUMBUHAN TANAMAN KEDELAI HITAM (Glycine soja L) MELALUI POC AIR TAHU DAN AIR KELAPA - Rahma Dina; Isnaini Nurwahyuni; Elimasni Elimasni (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2022)
The Study aims to see used of POC from tofu and coconut water waste has a significant effect in the growth of black soybean (Glycin soja L.) on the parameters of stem height, number of branches and leaves, and the number of stem diameters of black soybean plants. The research was conducted from September to December 2021 in kayu besar street, Batangkuis district. The study used RAK on 2 factorials, namely the treatment of giving POC from tofu and coconut water and concentrations at the levels of 0%, 15%, 20%, and 25%.The data analysis technique used the one way ANOVA test at a significant level of 5%and the DMRT test. The results showed that the use of POC from coconut air and air had a significantly different effect at a concentration of 25% better than other concentrations, namely 20%, 15%, and 0%. This study gave a better effect on the use of POC than those without fertilizers due to the addition of nutrients provided to increase the growth of black soybean plants.Key words: Black Soybean, POC, Water Tofu, Water Coconut.Â